1996
DOI: 10.1016/0022-0981(95)00153-0
|View full text |Cite
|
Sign up to set email alerts
|

Allorecognition responses in the soft coral Parerythropodium fulvum fulvum from the Red Sea

Abstract: Allorecognition responses in the soft coral Parerythropodium fulvum fulvum from the Red Sea. Frank, U.; Bak, R.P.M.; Rinkevich, B. Published in: Journal of Experimental Marine Biology and Ecology Link to publication Citation for published version (APA):Frank, U., Bak, R. P. M., & Rinkevich, B. (1996). Allorecognition responses in the soft coral Parerythropodium fulvum fulvum from the Red Sea. Journal of Experimental Marine Biology and Ecology, (197),[191][192][193][194][195][196][197][198][199][200][201]. Gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 30 publications
1
9
0
2
Order By: Relevance
“…The results of fusion between young organisms confirm earlier findings on hard corals (Hidaka 1985, Frank et al 1996, and suggest an ubiquitous pattern of alloimmune maturation in the Cnidaria.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…The results of fusion between young organisms confirm earlier findings on hard corals (Hidaka 1985, Frank et al 1996, and suggest an ubiquitous pattern of alloimmune maturation in the Cnidaria.…”
Section: Discussionsupporting
confidence: 80%
“…To evaluate the possible existence of an ontogenetic window that allows the development of natural chimeras in other members of cnidarians, we investigated allogenic responses in juveniles and adults of 4 soft coral species from the Red Sea, Clavularia hamra, Nepthea sp., Heteroxenia fuscescens and Parerythropodium fulvum fulvum. Although tissue fusions have never been recorded during numerous allogenic assays of adult colonies in the field or under laboratory conditions (Frank et al 1996, Barki 1999, we found that planula larvae and young (< 3 mo) polyps of all the above alcyonarian species can spontaneously fuse upon contact, forming natural chimeras. Fusions occurred either between kin larvae and young polyps originating from the same mother colony or between juveniles released from different genotypes (Barki 1999).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…The existence of an allorecognition system is welldocumented in adult coral species: genetically identical grafts (autografts) fuse, whereas genetically different grafts (allografts and xenografts) rarely fuse and show various histoincompatible responses (Chornesky 1991, Chadwick-Furman & Rinkevich 1994, Jokiel & Bigger 1994, Frank et al 1996.…”
Section: Introductionmentioning
confidence: 99%
“…irtually all multicellular organisms possess recognition systems that allow them to distinguish self from non-self with precision (1)(2)(3)(4). For example, self͞non-self recognition systems enable the prevention of inbreeding by self-pollination in plants (4)(5) as well as the cooperation between kin in various clonal marine invertebrates (6)(7)(8).…”
mentioning
confidence: 99%